(untitled) (London Journal of Medical and Health Research, 2024)
An aneurysm at the fenestration position of the basilar artery is an extremely rare condition that presents challenges in treatment. Aneurysm recurrence is a complication that can occur after interventions for aneurysms in this location. We report the case of a 43-year-old male patient with a ruptured basilar artery aneurysm treated with coils. After 30 months of follow-up, the aneurysm recurred and was treated with a flow diverter stent combined with coils.